Analisis Upper Bound dan Lower Bound pada Kuat Tekan Batupasir Formasi Balikpapan dan Pulau Balang dengan Metode Uniaxial Compressive Strength, Point Load Index dan Schmidt Hammer - Aisyatur Ridho; Tommy Trides; Rety Winonazada; Albertus Juvensius Pontus; Revia Oktaviani (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
Sandstone is one of the sedimentary rock types widely utilized in mining activities; therefore, its mechanical characteristics, particularly uniaxial compressive strength, need to be determined. This study aims to analyze the compressive strength of sandstone from the Balikpapan and Pulau Balang Formations using the Uniaxial Compressive Strength (UCS), Point Load Index (PLI), and Schmidt Hammer methods. Sampling and Schmidt Hammer testing were conducted in the field, while physical property tests, UCS tests, and PLI tests were carried out in the laboratory. The results indicate that the compressive strength of sandstone from the Pulau Balang Formation is higher than that of the Balikpapan Formation, with values ranging from 18.30–44.11 MPa and 10.05–39.51 MPa, respectively. The relationship between PLI and UCS for the Balikpapan Formation is expressed by the regression equation UCS = 16.569(Is50) with R² = 0.78, whereas for the Pulau Balang Formation the equation is UCS = 8.2664(Is50) with R² = 0.76. The regression equations were further complemented with upper and lower bounds based on the margin of error. In addition, the Rebound Number (Rn) exhibited a positive linear correlation with UCS, with coefficients of determination (R²) of 0.89 for the Balikpapan Formation and 0.98 for the Pulau Balang Formation. These findings indicate that higher UCS values correspond to higher Rebound Number values.